Response of Soybean Grown on a Claypan Soil in Southeastern Kansas to the Residual of Different Plant Nutrient Sources and Tillage - D. W. Sweeney; P. Barnes; G. Pierzynski (Kansas Agricultural Experiment Station Research Reports, 2019)
The residual from previous high-rate turkey litter applications, which were based on nitrogen (N) requirements of the previous grain sorghum crop, increased 2018 soybean yield more than that obtained from the residual of phosphorus (P)-based turkey litter applications (low rate), commercial fertilizer, or the control. Even though early soybean growth was sporadically affected by residual treatments, the dry matter production at the R6 growth stage tended to be where the N-based litter was applied.
Keywords: soybean; turkey litter; fertilizer; residual; tillage